Construct-Specific Loop-Mediated Isothermal Amplification: Rapid Detection of Genetically Modified Crops with Insect Resistance or Herbicide Tolerance. (26th March 2020) - Singh, Monika; Pal, Deepa; Sood, Payal; Randhawa, Gurinderjit
Abstract: Background: Insect resistant and herbicide tolerant genetically modified (GM) events have been approved in many countries. Screening methods could facilitate preliminary testing to check the GM status, which may target control elements, transgenes, and marker genes or construct regions. Among these, methods targeting the construct region, i.e., the junction between two genetic elements of a transgenic cassette are more specific. Objective: Loop-mediated isothermal amplification (LAMP) assays targeting three construct regions were developed; between Cauliflower Mosaic Virus 35S promoter and cry1Ac gene ( p35S-cry1Ac ), cry2Ab2 gene and nos terminator ( cry2Ab2-tnos ), and cp4-epsps gene and nos terminator ( cp4epsps-tnos ). Method: LAMP assays were performed by incubation at constant temperatures for selected targets. Positive amplification was detected as a change in color from orange to green on addition of SYBR ® Green dye in visual LAMP and as real-time amplification curves in real-time LAMP. Results: These assays showed acceptable specificity and sensitivity. Visual LAMP was found to be sensitive enough to detect as low as 0.005%, equivalent to two target copies. Real-time LAMP assays were able to detect as low as four copies of the target within 40 min, making them suitable for rapid on-site testing for GM organisms (GMO). Practical utility was also verified using spiked test samples. Conclusions: These assays could be employed to address some of the biosafety or post-release monitoring issues, as well as to check for approved and unapproved GM events in a country. Highlights: LAMP assays targeting three construct regions have been developed, enabling screening for approved or unapproved GMO.